Dielectric composition and multilayer ceramic electronic component
By adding specific dielectric particles containing Ca and Sr and segregated phases of Mn, Si, O to the dielectric composition, the problems of cracks and defects in the stacked ceramic electronic parts are solved, the destructive toughness and insulation breakdown voltage are improved, and the Durability.
Patent Information
- Application Number
- CN202310008376.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-04
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-01-04
AI Technical Summary
In the existing stacked ceramic electronic parts, the dielectric composition is prone to cracks or defects in the corners of the body, resulting in a decrease in characteristics and it is difficult to effectively suppress the occurrence of cracks and defects.
Using dielectric particles containing Ca and/or Sr, and adding Mn, Si, O and segregated phase selected from Ca and Sr, the content rate and average particle size of the segregated phase are controlled to improve the destructive toughness of the dielectric composition. Strength, inhibit the occurrence of cracks and defects.
By increasing the destructive toughness strength of the dielectric composition, cracks and defects of the ceramic layer are significantly suppressed, durability to external stress and impact is enhanced, and insulation breakdown voltage is improved.
Smart Images

Figure CN116504438B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a dielectric composition and a multilayer ceramic electronic component including the dielectric composition. Background Art
[0002] As shown in patent document 1, a laminated ceramic electronic component having a ceramic layer composed of a dielectric composition is known. In the laminated ceramic electronic component, cracks may occur inside the element body containing the dielectric composition or the corners of the element body may be defective. As the main causes of the cracks and defects, the deflection of the mounting substrate, the difference in linear expansion coefficients between the ceramic layer and the internal electrode layer, or the impact and stress applied to the element body from the outside are considered. If cracks and defects occur on the element body, the characteristics of the laminated ceramic electronic component are reduced, and therefore, it is required to improve the fracture toughness strength of the dielectric composition to suppress the occurrence of cracks and defects.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2002 / 000568 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a dielectric composition that is less likely to be cracked or chipped, and a multilayer ceramic electronic component including the dielectric composition.
[0008] Technical solutions to solve problems
[0009] In order to achieve the above object, the present invention provides a dielectric composition having:
[0010] Dielectric particles containing Ca and / or Sr;
[0011] A segregation phase containing Mn, Si, O, and at least one selected from Ca and Sr.
[0012] The present inventors have conducted intensive studies and have found that a dielectric composition having the above-mentioned characteristics can achieve high fracture toughness strength and can suppress the occurrence of cracks and defects.
[0013] Preferably, the dielectric particles contain a perovskite compound represented by ABO3,
[0014] The A site of the perovskite compound contains Ca and / or Sr, and the B site contains Zr and / or Ti.
[0015] The total molar ratio of Ca and Sr relative to 1 mol of the A site is 0.8 or more,
[0016] The molar ratio of Zr is 0.8 or more per 1 mol of the B site.
[0017] In the segregation phase and the dielectric particles, the content of the specified element is preferably controlled within a specified range. In the description of the content shown below, Ca, Sr, Zr, Mn, Si, Al, Ti and Hf are set as specific elements, and the total content of the specific elements in the segregation phase is set to 100 mol% to represent the content of the specified element in the segregation phase. In addition, the total content of the specific elements in the dielectric particles is set to 100 mol% to represent the content of the specified element in the dielectric particles.
[0018] Preferably, the content of Mn in the segregated phase is 5 mol% or more, and the content of Mn in the dielectric particles is 2 mol% or less.
[0019] By controlling the content of Mn in the segregation phase and the dielectric particles within the above range, cracks and defects can be more effectively suppressed, and a high dielectric breakdown voltage can be obtained.
[0020] Preferably, the total content of Ca and Sr in the segregation phase is 60 mol % or more.
[0021] Preferably, the content of Si in the segregation phase is 20 mol % or more.
[0022] Preferably, the content of the segregated phase is 0.05 pieces / μm 2 Above and 0.5 / μm 2 By controlling the content of the segregation phase within the above range, cracks and defects can be more effectively suppressed, and a high dielectric breakdown voltage can be obtained.
[0023] Preferably, the average grain size of the segregation phase is 0.05 μm or more and 1.00 μm or less. By controlling the average grain size of the segregation phase within the above range, cracks and defects can be more effectively suppressed, and a high dielectric breakdown voltage can be obtained.
[0024] The multilayer ceramic electronic component including the above-mentioned dielectric composition exhibits high durability against external stress and impact. That is, in the multilayer ceramic electronic component of the present invention, the occurrence of defects such as cracks and fissures in the element body can be sufficiently suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram showing a cross section of a multilayer ceramic capacitor according to one embodiment of the present invention.
[0026] Figure 2 Is magnification Figure 1 A cross-sectional view of a ceramic layer 10 is shown. DETAILED DESCRIPTION
[0027] In this embodiment, as an example of the ceramic electronic component of the present invention, Figure 1 The multilayer ceramic capacitor 2 shown in FIG. 1 is described below. The multilayer ceramic capacitor 2 includes a device body 4 and a pair of external electrodes 6 formed on the outer surface of the device body 4 .
[0028] Figure 1 The shape of the component body 4 shown is generally a roughly rectangular parallelepiped, and has two end faces 4a opposite in the X-axis direction, two side faces 4b opposite in the Y-axis direction, and two side faces 4b opposite in the Z-axis direction. However, the shape of the component body 4 is not particularly limited, and it can also be an elliptical column, a cylindrical shape, or other prism shapes. In addition, the outer dimensions of the component body 4 are not particularly limited. For example, the length L0 in the X-axis direction can be set to 0.4mm~5.7mm, the width W0 in the Y-axis direction can be set to 0.2mm~5.0mm, and the height T0 in the Z-axis direction can be set to 0.2mm~3.0mm. In addition, in this embodiment, the X-axis, the Y-axis, and the Z-axis are perpendicular to each other.
[0029] Furthermore, the element body 4 has a ceramic layer 10 and an internal electrode layer 12 that are substantially parallel to a plane including the X-axis and the Y-axis, and the ceramic layer 10 and the internal electrode layer 12 are alternately stacked along the Z-axis direction inside the element body 4. Here, "substantially parallel" means that most of them are parallel, but there may be slightly non-parallel parts, and the ceramic layer 10 and the internal electrode layer 12 may also be slightly concave and convex or inclined.
[0030] The ceramic layer 10 is composed of a dielectric composition described later. Moreover, the average thickness (interlayer thickness) of each layer of the ceramic layer 10 is not particularly limited, and for example, it can be set to 100 μm or less, and preferably 30 μm or less. In addition, the number of stacked layers of the ceramic layer 10 can be determined according to the desired characteristics and is not particularly limited. For example, it can be set to 20 layers or more, and more preferably 50 layers or more.
[0031] On the other hand, the internal electrode layer 12 is stacked between the ceramic layers 10, and the number of stacked layers is determined by the number of stacked ceramic layers 10. The average thickness of each internal electrode layer 12 is not particularly limited, and can be set to 3.0 μm or less, for example. The average thickness of the ceramic layer 10 or the average thickness of the internal electrode layer 12 is observed by using a metal microscope. Figure 1 The thickness of each layer (10, 12) can be calculated by measuring the cross section shown in the figure at least in five locations.
[0032] In addition, the internal electrode layer 12 is stacked in a manner in which one end portion is alternately exposed on two end surfaces 4a of the element body 4 that are opposite in the X-axis direction. Moreover, a pair of external electrodes 6 are respectively formed on one end surface 4a of the element body 4, and are electrically connected to the exposed ends of the alternately arranged internal electrode layers 12. By forming the internal electrode layer 12 and the external electrode 6 in this way, a capacitor circuit is constituted by the external electrode 6 and the internal electrode layer 12. That is, the ceramic layer 10 existing in the capacitor region is sandwiched by the internal electrode layers 12 with different polarities, and a voltage can be applied to the ceramic layer 10.
[0033] The internal electrode layer 12 is made of a conductive material, preferably containing Ni as a main component. Specifically, the conductive material of the internal electrode layer 12 is preferably pure Ni or a Ni-based alloy containing 85wt% or more of Ni, and the Ni-based alloy may also contain one or more elements selected from Mn, Cu, Cr, etc. In addition, in addition to the above-mentioned conductive materials, the internal electrode layer 12 may also contain particles of a perovskite compound having the same composition as the main component of the ceramic layer 10 as a common material. Moreover, the internal electrode layer 12 may also contain a trace amount (for example, less than 0.1 mass%) of non-metallic components such as S and P, and may also contain voids. In addition, when the internal electrode layer 12 contains a common material, voids, etc., a discontinuity where no electrode (conductive material) is present may be formed in the internal electrode layer 12.
[0034] A pair of external electrodes 6 may include a sintered electrode layer, a resin electrode layer, a plated electrode layer, etc., and may be composed of a single electrode layer or a plurality of electrode layers. For example, the external electrode 6 may be a three-layer structure of a sintered electrode layer containing Cu, a Ni-plated layer, and a Sn-plated layer (stacked in the order described). In the case of forming the external electrode 6 of the three-layer structure, since the Sn-plated layer is located on the outermost surface of the external electrode 6, the solder wettability of the external electrode 6 is good.
[0035] In addition, if Figure 1 As shown, the external electrode 6 integrally includes an end face portion formed on the end face 4a in the X-axis direction of the element body 4, and an extension portion formed on the four side faces 4b of the element body 4 at the end portion in the X-axis direction. That is, a pair of external electrodes 6 are formed in a manner of wrapping around the side faces 4b from the end face 4a of the element body 4, and are insulated in a manner not to contact each other in the X-axis direction.
[0036] In addition, the extension portion of the external electrode 6 is not essential, and the external electrode 6 may be composed of only the end surface portion. Alternatively, when the multilayer ceramic capacitor 2 is surface mounted on a substrate, the extension portion of the external electrode 6 only needs to be formed on at least the side surface 4b facing the mounting surface of the substrate, and may not be formed on the side surface 4b opposite to the mounting surface.
[0037] Next, the dielectric composition of the ceramic layer 10 will be described in detail.
[0038] The dielectric composition of the ceramic layer 10 includes a main component containing Ca and / or Sr, and the main component is preferably a perovskite compound represented by the general formula ABO3. Here, the main component of the ceramic layer 10 (the main component of the dielectric composition) means a component that accounts for 80 mol% or more in the ceramic layer 10. Examples of the perovskite compound include barium titanate, calcium titanate, strontium titanate, calcium zirconate, strontium zirconate, and calcium strontium zirconate.
[0039] In this embodiment, the perovskite compound as the main component preferably satisfies the composition formula (Ca (1-α-β) Sr α Ba β ) m (Zr (1-γ-δ) Ti γ Hf δ )O3. In the above composition formula, the symbols α, β, γ, δ, and m represent element ratios, respectively.
[0040] m represents the element ratio of the A site to the B site, and can be in the range of 1.0 to 1.1.
[0041] α represents the element ratio of Sr in the A site, and β represents the element ratio of Ba in the A site. In the present embodiment, it is preferred that the A site is mainly composed of Ca and / or Sr. Specifically, the total ratio (1-β) of Ca and Sr in the A site is preferably greater than 0.8. In addition, the element ratio (1-α-β) of Ca at the A site is preferably greater than 0.5 and less than 1.0, more preferably greater than 0.6 and less than 1.0. α is preferably greater than 0 and less than 0.5, more preferably greater than 0 and less than 0.4. β is preferably greater than 0 and less than 0.2, more preferably less than 0.1.
[0042] γ represents the element ratio of Ti in the B site, and δ represents the element ratio of Hf in the B site. In the present embodiment, it is preferred that the B site is mainly composed of Zr. Specifically, the element ratio (1-γ-δ) of Zr at the B site is preferably greater than 0.8 and less than 1.0, more preferably greater than 0.9 and less than 1.0. γ is preferably greater than 0 and less than 0.2, more preferably less than 0.1. Hf is generally an unavoidable impurity, and δ is preferably less than 0.03.
[0043] Furthermore, the element ratio of oxygen (O) in the above composition formula may slightly deviate from the stoichiometric composition.
[0044] In addition to the above-mentioned main components, the ceramic layer 10 may also contain auxiliary components. Examples of the auxiliary components include Mn compounds, Mg compounds, Cr compounds, Ni compounds, compounds containing rare earth elements, Si compounds, Li compounds, B compounds, V compounds, Al compounds, Ca compounds, etc. The types, combinations, and addition amounts of the auxiliary components are not particularly limited.
[0045] In addition, the component composition of the ceramic layer 10 can be analyzed by an electron beam microanalyzer (EPMA) with inductively coupled plasma emission spectroscopy (ICP), laser ablation ICP mass spectrometry (LA-ICP-MS), fluorescent X-ray analysis (XRF), energy dispersive X-ray analysis (EDX), wavelength dispersive X-ray spectrometer (WDS), etc.
[0046] The ceramic layer 10 including the above-mentioned components has Figure 2 The internal structure shown in the figure includes dielectric particles 20 as a parent phase, segregation phases 21 having predetermined characteristics, and grain boundaries 22 located between the dielectric particles 20 in the ceramic layer 10. In addition, the grain boundaries 22 include grain boundary multiple points 22a located between three or more dielectric particles 20 and two-grain grain boundaries 22b located between two dielectric particles 20.
[0047] The dielectric particles 20 are composed of the main component (perovskite compound) of the above-mentioned ceramic layer 10. When the ceramic layer 10 contains a secondary component, the secondary component may be solid-dissolved in the dielectric particles 20 in addition to the main component. In addition, the dielectric particles 20 may also have a core-shell structure by solid-dissolving the secondary component. The average particle size of the dielectric particles 20 may be set to 5 μm or less, and preferably 0.10 μm to 2.00 μm.
[0048] The average particle size of the dielectric particles 20 can be determined by observing the average particle size of the dielectric particles 20 using a scanning transmission electron microscope (STEM), a scanning electron microscope (SEM), or the like. Figure 2 The cross section of the ceramic layer 10 as shown in the figure is measured by image analysis of the obtained cross section photograph. For example, the average particle size of the dielectric particles 20 can be calculated by measuring the equivalent circle diameters of at least five dielectric particles 20.
[0049] In the ceramic layer 10 of this embodiment, as Figure 2As shown, it includes a segregation phase 21. The segregation phase 21 contains Mn, Si, O (oxygen), and at least one selected from Ca and Sr. That is, the segregation phase 21 is a phase containing a ternary composite oxide (Ca-Mn-Si-O or Sr-Mn-Si-O) or a quaternary composite oxide (Ca-Sr-Mn-Si-O). In addition to the above-mentioned elements, the segregation phase 21 may also contain Ba, Zr, Ti, Hf, Al and accessory elements. By having the segregation phase 21 containing the prescribed elements in the dielectric composition, the fracture toughness strength of the dielectric composition is improved, and the occurrence of defects such as cracks and defects in the ceramic layer 10 can be suppressed. In addition, the segregation phase 21 is preferably present at the grain boundary multiple points 22a compared to the two-grain grain boundary 22b.
[0050] The segregation phase 21 can be determined by mapping analysis using STEM-EDS, STEM-WDS, SEM-EDX or SEM-WDS. Figure 2 In the cross section of the element body 4 as shown, mapping analysis is performed to obtain a mapping image of each element constituting the dielectric composition. In the mapping image, the area where the existence ratio of the specified element is high, that is, the area where the specified element is segregated, can be determined based on the depth of the color tone. In particular, in the segregation phase 21, the concentration of Ca and / or Sr, the concentration of Mn, and the concentration of Si are higher than those in the dielectric particles 20. Therefore, the mapping images of Ca, Sr, Mn, and Si are overlapped, and the area where Ca and / or Sr, Mn, and Si are repeatedly segregated is determined, and this area is identified as the segregation phase 21 in this embodiment.
[0051] In addition, in order to more accurately determine whether Ca and Sr are contained in the segregation phase 21, it is preferable to perform point analysis together with the above-mentioned mapping analysis. That is, in a specific area identified as the segregation phase 21 by mapping analysis, point analysis using STEM-EDS, STEM-WDS, SEM-EDX or SEM-WDS is performed. Ca and Sr are elements constituting the main components of the ceramic layer 10, and in the point analysis of a specific area, they are affected by the dielectric particles 20 present around the specific area. Therefore, when investigating whether Ca and Sr are contained in the segregation phase 21 by EDX and WDS, the molar ratio of Ca to the total of Zr and Ti (Ca / (Zr+Ti)) and the molar ratio of Sr to the total of Zr and Ti (Sr / (Zr+Ti)) are measured.
[0052] Specifically, Ca / (Zr+Ti) in a specific region and Ca / (Zr+Ti) in the dielectric particles 20 are measured and compared. When Ca / (Zr+Ti) in a specific region is higher than that in the dielectric particles 20, it can be determined that Ca is contained in the specific region, and it can be determined that the specific region is the segregation phase 21 in the present embodiment. Similarly, Sr / (Zr+Ti) in a specific region and Sr / (Zr+Ti) in the dielectric particles 20 are measured and compared. When Sr / (Zr+Ti) in a specific region is higher than that in the dielectric particles 20, it can be determined that Sr is contained in the specific region, and it can be determined that the specific region is the segregation phase 21 in the present embodiment.
[0053] In the segregation phase 21, the content of the constituent elements is preferably controlled within a predetermined range. In the description related to the "content" shown below, Ca, Sr, Zr, Mn, Si, Al, Ti, and Hf are set as specific elements, and the total content of the specific elements in the segregation phase 21 is set to 100 mol% to represent the content of the specified elements in the segregation phase 21. Similarly, the total content of the specific elements in the dielectric particles 20 is set to 100 mol% to represent the content of the specified elements in the dielectric particles 20.
[0054] First, regarding Mn as a constituent element of the segregation phase 21, it is preferred that the content of Mn in the segregation phase 21 is 5 mol% or more, and it is preferred that the content of Mn in the dielectric particles 20 is 2 mol% or less. By controlling the content of Mn in both the segregation phase 21 and the dielectric particles 20 within the above range, cracks and defects can be more effectively suppressed, and a high dielectric breakdown voltage can be obtained. In addition, the content of Mn in the segregation phase 21 is more preferably 7 mol% or more, and the upper limit is not particularly limited. For example, the content of Mn in the segregation phase 21 can be set to 15 mol% or less, and is preferably set to 10 mol% or less. In addition, the content of Mn in the dielectric particles 20 is more preferably 1 mol% or less, and more preferably 0.5 mol% or less.
[0055] The total content of Ca and Sr in the segregation phase 21 is preferably 60 mol% or more. By satisfying this requirement, it is possible to maintain a high insulation breakdown voltage and more effectively suppress cracks and defects. In addition, the upper limit of the total content of Ca and Sr in the segregation phase 21 is not particularly limited, for example, it is preferably 70 mol% or less. In addition, when both Ca and Sr are contained in the segregation phase 21, the Ca / Sr ratio in the segregation phase 21 is preferably 1.5 or more, and more preferably 1.5 or more and 8 or less.
[0056] The content of Si in the segregation phase 21 is preferably 20 mol% or more, more preferably 22 mol% or more. By satisfying this requirement, it is possible to maintain a high insulation breakdown voltage and more effectively suppress cracks and defects. In addition, the upper limit of the content of Si in the segregation phase 21 is not particularly limited, for example, it is preferably 35 mol% or less, more preferably 31 mol% or less.
[0057] The detailed composition of the segregation phase 21 is not particularly limited, but the crystal structure of the segregation phase 21 is preferably orthorhombic. As a composite oxide having such a crystal structure, for example, (Ca, Sr, Mn) 2 SiO 4 can be cited. In this composite oxide, Ca, Sr and Mn share the same site.
[0058] The average particle size of the segregation phase 21 is preferably 0.05 μm or more and 1.00 μm or less, and more preferably 0.08 μm or more and 0.85 μm or less. In addition, the average particle size of the segregation phase 21 is preferably in the range of 0.05 to 0.5 times the average particle size of the dielectric particles 20. The average particle size of the segregation phase 21 can be calculated by determining at least five or more segregation phases 21 using EDX or WDS, and then measuring the equivalent circle diameter of the determined segregation phases 21 using image analysis.
[0059] In the present embodiment, the content of the segregation phase 21 in the dielectric composition (ie, the ceramic layer 10) is expressed as the number of segregation phases 21 contained per unit cross-sectional area of the dielectric composition (unit: number / μm 2 The content of the segregation phase 21 can be set to 0.01 per μm. 2 Above, preferably 0.05 pieces / μm 2 Above and 0.50 pieces / μm 2 In addition, the content of the segregation phase 21 was observed in multiple fields of view using STEM and SEM. Figure 2 The cross section of the ceramic layer 10 shown in FIG. 1 is measured to exist in a total area of at least 1000 μm. 2 The calculation can be performed based on the number of the segregation phases 21 in the above cross section.
[0060] When the average grain size and content of the segregation phase 21 satisfy the above-mentioned preferred ranges, cracks and defects can be more effectively suppressed while maintaining a high breakdown voltage.
[0061] As described above, the ceramic layer 10 (dielectric composition) of the present embodiment includes a predetermined segregation phase 21, and the fracture toughness strength of the element body 4 can be improved by the segregation phase 21. In addition, in addition to the above-mentioned segregation phase 21, other segregation phases, voids, etc. may also exist on the ceramic layer 10. As other segregation phases, segregation phases containing Zr and segregation phases containing auxiliary component elements such as Mg, Al or rare earth elements can be cited. In addition, regarding the grain boundaries 22 existing between the dielectric particles 20, they are composed of the constituent elements of the main component and the auxiliary component elements, and other segregation phases such as the above-mentioned may exist at the grain boundaries 22.
[0062] Next, Figure 1 An example of a method for manufacturing the multilayer ceramic capacitor 2 shown in FIG.
[0063] First, the manufacturing process of the element body 4 will be described. In the manufacturing process of the element body 4, a dielectric paste that becomes the ceramic layer 10 after firing and an internal electrode paste that becomes the internal electrode layer 12 after firing are prepared.
[0064] The dielectric paste is manufactured using a powder of a perovskite compound as a main component of the dielectric composition (hereinafter referred to as the main component powder) and a segregation powder that becomes a segregation phase 21 after firing. The main component powder can be manufactured by a solid phase method, a hydrothermal synthesis method, or a sol-gel method. For example, in the solid phase method, starting materials such as CaCO3 powder, SrCO3 powder, ZrO2 powder, and TiO2 powder are uniformly mixed by wet mixing or the like, and then pre-fired to obtain the main component powder. At this time, the pre-fired main component powder can also be appropriately pulverized, classified, and the like.
[0065] The segregation powder is obtained by mixing a compound powder containing Ca (e.g., CaCO3 powder) and / or a compound powder containing Sr (e.g., SrCO3 powder), a compound powder containing Mn (e.g., MnCO3 powder), and a compound powder containing Si (e.g., SiO2 powder) in a predetermined ratio and pre-calcining. The composition of the segregation phase 21 can be controlled by the mixing ratio of each compound powder as a starting material. In addition, when manufacturing the segregation powder, it is preferred to appropriately perform a pulverization process and control the particle size of the segregation phase 21. In addition, as each compound powder, oxide powder, carbonate powder, nitrate powder, sulfate powder, etc. can be used, as long as a powder of a compound that becomes an oxide after calcination is used.
[0066] The dielectric paste is obtained by adding the above-mentioned main component powder and segregation powder to an organic vehicle and kneading them. Here, the organic vehicle is a substance obtained by dissolving a binder in an organic solvent. The binder used is not particularly limited, for example, it can be appropriately selected from various binders such as polyvinyl butyral, acrylic acid, ethyl cellulose, etc. In addition, the organic solvent used is also not particularly limited, for example, it can be appropriately selected from various organic solvents such as methyl ethyl ketone, methanol, ethanol, acetone, toluene, terpineol, butyl carbitol, etc.
[0067] In addition, the above-mentioned dielectric paste is an organic coating, and the dielectric paste can also be an aqueous coating obtained by kneading a mixed powder and an aqueous carrier. In this case, the aqueous carrier is prepared by dissolving a water-soluble adhesive, a dispersant, etc. in water. The water-soluble adhesive used is not particularly limited, for example, polyvinyl alcohol, a water-soluble acrylic resin, a water-soluble polyvinyl butyral resin, etc. can be used. By adjusting the proportion of the segregation powder in the dielectric paste, the content of the segregation phase 21 can be controlled. In addition, the dielectric paste can also contain additives selected from various dispersants, plasticizers, dielectrics, accessory components, glass frits, etc. as needed.
[0068] On the other hand, the internal electrode paste is prepared by kneading conductive materials such as pure Ni powder, Ni alloy powder, or various oxides, organic metal compounds, resinates, etc. that become the above-mentioned Ni and Ni alloys after formal firing, together with the above-mentioned organic carrier. At this time, the main component powder contained in the dielectric paste can also be added to the internal electrode paste as a common material. The common material plays a role in suppressing the sintering of the conductive powder during the firing process.
[0069] Next, the dielectric paste is sliced by a doctor blade method or the like to obtain a ceramic green sheet. Then, the internal electrode paste is applied to the ceramic green sheet in a predetermined pattern by various printing methods such as screen printing or transfer methods. Furthermore, after the green sheets with the internal electrode pattern formed are stacked multiple times, they are pressed in the stacking direction to obtain a mother laminate. In addition, at this time, the ceramic green sheets and the internal electrode pattern are stacked in such a way that the ceramic green sheets are located on the upper and lower surfaces of the mother laminate in the stacking direction.
[0070] The mother laminate obtained by the above-mentioned process is cut into a specified size by cutting and pressing to obtain a plurality of green chips. The green chips can also be cured and dried as needed to remove plasticizers, etc., or can be drum-ground using a horizontal centrifugal drum machine, etc. after curing and drying. In drum grinding, the green chips are put into a drum container together with a medium and a grinding liquid, and rotational motion, vibration, etc. are applied to the drum container. Through the drum grinding, unnecessary parts such as burrs generated during cutting are ground, and fillets (angles R) are formed at the corners of the green chips. The green chips after drum grinding are cleaned with a cleaning solution such as water and dried. In addition, the drum grinding can also be implemented after the green chips are fired.
[0071] Next, the green chip obtained as described above is subjected to a binder removal process and a firing process to obtain the element body 4 .
[0072] The conditions for the binder removal treatment are not particularly limited, and may be appropriately determined according to the main component composition of the ceramic layer 10 and the main component composition of the internal electrode layer 12. For example, the heating rate is preferably set to 5 to 300°C / hour, the holding temperature is preferably set to 180 to 400°C, and the temperature holding time is preferably set to 0.5 to 24 hours. In addition, the binder removal atmosphere is set to air or a reducing atmosphere.
[0073] The conditions for the sintering treatment are not particularly limited, and can be appropriately determined based on the main component composition of the ceramic layer 10 and the main component composition of the internal electrode layer 12. For example, the holding temperature during sintering is preferably 1200-1350°C, more preferably 1220-1300°C, and the holding time is preferably 0.5-8 hours, more preferably 1-3 hours. In addition, the sintering atmosphere is preferably a reducing atmosphere, and as the atmosphere gas, for example, a mixed gas of N2 and H2 can be used in a humidified state. Moreover, when the internal electrode layer 12 is composed of a base metal such as Ni or a Ni alloy, it is preferred that the oxygen partial pressure in the sintering atmosphere be 1.0×10 -14 ~1.0×10 -10 MPa.
[0074] In addition, after the firing treatment, annealing may be performed as needed. Annealing is a treatment for reoxidizing the ceramic layer 10, and is preferably performed when the firing treatment is performed in a reducing atmosphere. The conditions for the annealing treatment are not particularly limited, and may be appropriately determined based on the main component composition of the ceramic layer 10. For example, it is preferred to set the holding temperature to 650 to 1150°C, the temperature holding time to 0 to 20 hours, and the heating rate and cooling rate to 50 to 500°C / hour. In addition, the atmosphere gas is preferably dry N2 gas or humidified N2 gas, etc. In addition, annealing may be performed multiple times.
[0075] In the above-mentioned binder removal treatment, firing treatment and annealing treatment, in order to humidify N2 gas, mixed gas, etc., for example, a humidifier may be used, in which case the water temperature is preferably about 5 to 75° C. In addition, the binder removal treatment, firing treatment and annealing treatment may be performed continuously or independently.
[0076] In order to suppress the Mn content in the dielectric particles 20 to be as low as 2 mol % or less, the oxygen partial pressure in the firing atmosphere is preferably set to 1.0×10 -12 MPa or less. Alternatively, it is more preferable to set the oxygen partial pressure in the firing atmosphere to 1.0×10 -12 MPa or less and annealing is performed twice or more.
[0077] In each of the above-mentioned heat treatments (debinding treatment, firing treatment, annealing treatment (reoxidation treatment)), the green chip is placed on a plate-shaped refractory, i.e., a setter, and heated. Then, after the heat treatment, the fired element body 4 is dropped from the setter and recovered. In the present embodiment, the ceramic layer 10 is composed of a dielectric composition having a segregation phase 21, and cracks and defects are not likely to occur on the element body 4 even if an impact such as falling is applied. That is, when the fired element body 4 is recovered from the setter, cracks, defects, etc. can also be suppressed, and the defect rate in the manufacturing process can be reduced.
[0078] Next, a pair of external electrodes 6 are formed on the outer surface of the element body 4 obtained above. The method for forming the external electrodes 6 is not particularly limited. For example, in the case of forming sintered electrodes as the external electrodes 6, after applying a conductive paste containing glass frit to the end face of the element body 4 by a dipping method, the element body 4 can be heated at a predetermined temperature. In addition, in the case of forming resin electrodes as the external electrodes 6, a conductive paste containing a thermosetting resin is applied to the end face of the element body 4, and then the element body 4 is heated at a temperature at which the thermosetting resin is cured. In addition, after forming the sintered electrodes or the resin electrodes by the above method, sputtering, evaporation, electrolytic plating or electroless plating can be performed to form the external electrodes 6 having a multilayer structure.
[0079] Through the above-described steps, the multilayer ceramic capacitor 2 having the external electrodes 6 is obtained.
[0080] (Summary of Implementation Methods)
[0081] The multilayer ceramic capacitor 2 of the present embodiment has a component body 4 in which ceramic layers 10 composed of a predetermined dielectric composition and internal electrode layers 12 are alternately stacked. The dielectric composition of the ceramic layer 10 has: dielectric particles 20 containing Ca and / or Sr; and segregation phases 21 containing Mn, Si, O, and at least one selected from Ca and Sr.
[0082] The dielectric composition of the ceramic layer 10 has the above-mentioned characteristics, and the fracture toughness strength is improved. The reason for the improvement of the fracture toughness strength may not be clear, but it is considered that the bonding strength between the dielectric particles is improved by the segregation phase 21 containing the specified element. In addition, even if the starting point of a crack is generated inside the dielectric composition, the progress of the crack can be suppressed by the segregation phase 21. In the laminated ceramic capacitor 2 of the present embodiment, since the ceramic layer 10 is composed of a dielectric composition with high fracture toughness strength, the occurrence of cracks and defects on the element body 4 can be fully suppressed. In addition, the laminated ceramic capacitor 2 shows high durability against external stress and impact.
[0083] In particular, by controlling the content of each constituent element in the segregation phase 21, the average grain size of the segregation phase 21, the content of the segregation phase 21, etc. within a predetermined range, it is possible to maintain a high dielectric breakdown voltage and more effectively suppress cracks and defects.
[0084] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment, Various changes can be made within the range which does not deviate from the summary of this invention.
[0085] For example, in the present embodiment, the multilayer ceramic capacitor 2 is exemplified as the multilayer ceramic electronic component, but the multilayer ceramic electronic component of the present invention may be, for example, a bandpass filter, a multilayer three-terminal filter, a thermistor, a varistor, or the like.
[0086] In addition, in this embodiment, the ceramic layer 10 and the internal electrode layer 12 are stacked in the Z-axis direction, but the stacking direction may be in the X-axis direction or the Y-axis direction. In this case, the external electrode 6 may be formed according to the exposed surface of the internal electrode layer 12. In addition, the internal electrode layer 12 may be led out of the outer surface of the element body 4 via a through-hole electrode, in which case the through-hole electrode and the external electrode 6 are electrically connected.
[0087] Example
[0088] Hereinafter, the present invention will be described based on more detailed examples, but the present invention is not limited to these examples.
[0089] (Experiment 1)
[0090] In Experiment 1, capacitor samples of Examples 1 to 3 and Comparative Examples 1 to 5 were produced in the following procedure.
[0091] Example 1
[0092] First, a main component powder and a segregation powder as raw materials for a dielectric paste are prepared. Specifically, the main component powder is (Ca 0.7 Sr 0.3)(Zr 0.96 Ti 0.04 )O3 powder. On the other hand, the segregation powder is obtained by wet mixing CaCO3 powder, MnCO3 powder and SiO2 powder in a predetermined ratio, pre-calcining and then grinding with a ball mill. That is, in Example 1, a ternary composite oxide of Ca-Mn-Si-O is used as the segregation powder.
[0093] Next, the main component powder, the segregation powder, the organic vehicle and the auxiliary component powder (Al2O3 powder) are kneaded to obtain a dielectric paste. Also, Ni powder and the organic vehicle are kneaded to obtain an internal electrode paste.
[0094] Next, a green chip is manufactured by a sheet method using the above-mentioned dielectric paste and internal electrode paste. Then, the green chip is subjected to a binder removal process, a sintering process, and an annealing process to obtain a component body 4 having a size of L0×W0×T0=3.2mm×2.5mm×2.5mm. In addition, in the obtained component body 4, the number of stacked ceramic layers 10 sandwiched by the internal electrode layers 12 is set to 150, and the average thickness of the ceramic layers 10 is set to 12μm, and the average thickness of the internal electrode layers 12 is set to 1.4μm. Through the above steps, the capacitor sample of Example 1 is obtained.
[0095] Example 2
[0096] In Example 2, SrCO3 powder, MnCO3 powder and SiO2 powder were wet mixed at a predetermined ratio and pre-calcined and then pulverized with a ball mill to obtain a segregation powder. That is, in Example 2, the type of segregation powder was changed from that in Example 1, and a ternary composite oxide of Sr-Mn-Si-O was used as the segregation powder. The experimental conditions other than the above were the same as those in Example 1, and a capacitor sample of Example 2 was obtained.
[0097] Example 3
[0098] In Example 3, the segregation powder was obtained by wet mixing CaCO3 powder, SrCO3 powder, MnCO3 powder and SiO2 powder at a predetermined ratio, pre-calcining and then pulverizing with a ball mill. That is, in Example 3, the type of segregation powder was changed from that in Example 1, and a quaternary composite oxide of Ca-Sr-Mn-Si-O was used as the segregation powder. The experimental conditions other than the above were the same as those in Example 1, and the capacitor sample of Example 3 was obtained.
[0099] Comparative Example 1
[0100] In Comparative Example 1, a dielectric paste was prepared without using a segregation powder. That is, the dielectric paste in Comparative Example 1 was prepared by mixing (Ca 0.7 Sr0.3 )(Zr 0.96 Ti 0.04 )O3, a subcomponent powder (the same subcomponent as in Example 1), and an organic vehicle are mixed. The experimental conditions other than the above in Comparative Example 1 are the same as those in Example 1, and a capacitor sample of Comparative Example 1 is obtained.
[0101] Comparative Example 2
[0102] In Comparative Example 2, MnCO3 powder is added to the dielectric paste, and no segregation powder is used. That is, the dielectric paste in Comparative Example 2 is composed of (Ca 0.7 Sr 0.3 )(Zr 0.96 Ti 0.04 )O3, MnCO3 powder, other auxiliary component powders (the same auxiliary components as in Example 1) and an organic carrier are mixed. The experimental conditions other than the above in Comparative Example 2 are the same as those in Example 1, and a capacitor sample of Comparative Example 2 is obtained.
[0103] Comparative Example 3
[0104] In Comparative Example 3, MnCO3 powder and SiO2 powder are added to the dielectric paste, and no segregation powder is used. 0.7 Sr 0.3 )(Zr 0.96 Ti 0.04 )O3-based main component powder, MnCO3 powder, SiO2 powder, other auxiliary component powders (the same auxiliary components as in Example 1) and an organic vehicle were mixed to prepare a dielectric paste. The experimental conditions other than the above in Comparative Example 3 were the same as those in Example 1, and a capacitor sample of Comparative Example 3 was obtained.
[0105] Comparative Example 4
[0106] In Comparative Example 4, CaCO3 powder and SiO2 powder are added to the dielectric paste, and no segregation powder is used. 0.7 Sr 0.3 )(Zr 0.96 Ti 0.04 )O3, CaCO3, SiO2, other auxiliary component powders (the same auxiliary components as in Example 1) and an organic vehicle were mixed to prepare a dielectric paste. The experimental conditions other than the above in Comparative Example 4 were the same as those in Example 1, and a capacitor sample of Comparative Example 4 was obtained.
[0107] Comparative Example 5
[0108] In Comparative Example 5, SrCO3 powder and SiO2 powder are added to the dielectric paste, and no segregation powder is used. 0.7 Sr 0.3 )(Zr 0.96 Ti 0.04 )O3-based main component powder, SrCO3 powder, SiO2 powder, other auxiliary component powders (the same auxiliary components as in Example 1) and an organic vehicle were mixed to prepare a dielectric paste. The experimental conditions other than the above in Comparative Example 5 were the same as those in Example 1, and a capacitor sample of Comparative Example 5 was obtained.
[0109] The capacitor samples of each example and each comparative example in Experiment 1 were subjected to the following evaluations.
[0110] Analysis of segregation
[0111] The segregation phase present in the ceramic layer was analyzed by STEM-EDX. First, a thin slice sample was collected from the ceramic layer 10 located near the center of the element body by using a microsampling method using a focused ion beam (FIB), and the thin slice sample was processed into a thickness of less than 100 nm to obtain an analysis sample for cross-sectional observation. Then, the analysis sample was observed by STEM, and at this time, the constituent elements of the segregation phase present in the interior of the ceramic layer 10 were determined by performing mapping analysis and point analysis based on EDX. The measurement results in each embodiment and each comparative example are shown in Table 1.
[0112] Impact resistance test
[0113] In Experiment 1, the impact resistance test was performed on the fired samples (component bodies) of each embodiment and each comparative example. Specifically, the fired component body was dropped from a specified height, and the appearance of the dropped component body was checked using a real microscope. Under Condition 1, the drop height was set to 0.5m, and 100 samples of each embodiment and each comparative example were subjected to the impact resistance test. In addition, under Condition 2, the drop height was set to 2.0m, and 100 samples of each embodiment and each comparative example were subjected to the impact resistance test. In the appearance inspection after the test, the number of samples with cracks and corner defects on the component body was measured, and the defective incidence rate (%) was calculated. If the defective incidence rate in Condition 1 is 0%, it is judged to be "qualified", and if the defective incidence rate in Condition 2 is 0%, it is judged to be "particularly good" in impact resistance. The test results of each embodiment and each comparative example are shown in Table 1.
[0114] Dielectric breakdown voltage
[0115] In addition, in Experiment 1, the insulation breakdown voltage of the capacitor samples of each embodiment and each comparative example was measured. Specifically, the capacitor sample was placed in silicone oil at room temperature, a direct current was applied to the capacitor sample under the condition of a voltage increase rate of 100V / sec, and the voltage value at the moment when the leakage current exceeded 200mA was measured as the insulation breakdown voltage (V). Regarding the insulation breakdown voltage, samples above 1400V were judged as "good", and samples above 1450V were judged as "particularly good". The evaluation results in each embodiment and each comparative example are shown in Table 1.
[0116] Table 1
[0117]
[0118] As shown in Table 1, in Comparative Example 1 containing no segregation phase and Comparative Examples 2 to 5 containing segregation consisting of a mono- or binary oxide phase, samples were confirmed to have cracks and defects after being dropped from 0.5 m, and the impact resistance was insufficient. On the other hand, in Examples 1 to 3, segregation phases 21 containing Mn, Si, O, and at least one selected from Ca and Sr were confirmed, and in these Examples, no cracks or defects were generated after being dropped from 0.5 m. From this result, it can be seen that by including the segregation phase 21 in the dielectric composition constituting the ceramic layer 10, the occurrence of cracks and defects in the element body 4 can be suppressed.
[0119] In addition, when comparing Examples 1 to 3, Example 3 has the best impact resistance. From this result, it is known that it is preferable to contain both Ca and Sr rather than only one of Ca or Sr in the segregation phase 21. In addition, in Examples 1 to 3, it can be confirmed that the segregation phase 21 exists at the grain boundary multiple points 22a.
[0120] Experiment 2
[0121] In Experiment 2, the ratio of the constituent elements in the segregation phase 21 was changed to produce capacitor samples of Examples 4 to 14.
[0122] (Examples 4 to 8)
[0123] In Examples 4 to 8, the Mn content in the dielectric particles 20 and the segregation phase 21 was changed. When preparing the powder for segregation, the Mn content in the segregation phase 21 was controlled by adjusting the mixing ratio of the starting materials (CaCO3 powder, SrCO3 powder, MnCO3 powder and SiO2 powder). In addition, the Mn content in the dielectric particles 20 was controlled by adjusting the oxygen partial pressure in the sintering atmosphere. The experimental conditions other than the above were the same as those of Example 3 of Experiment 1, and capacitor samples of Examples 4 to 8 were prepared. The Mn content in each of Examples 4 to 8 was measured using STEM-EDX, and the capacitor samples of Examples 4 to 8 were evaluated in the same manner as in Experiment 1. The evaluation results of Examples 4 to 8 are shown in Table 2.
[0124] (Examples 9 to 11)
[0125] In Examples 9 to 11, the total content of Ca and Sr in the segregation phase 21 was changed. When preparing the powder for segregation, the total content of Ca and Sr was controlled by adjusting the mixing ratio of the starting materials (CaCO3 powder, SrCO3 powder, MnCO3 powder and SiO2 powder). The experimental conditions other than the above were the same as those of Example 3 of Experiment 1, and capacitor samples of Examples 9 to 11 were prepared. The total content of Ca and Sr in each of Examples 9 to 11 was measured using STEM-EDX, and the capacitor samples of Examples 9 to 11 were evaluated in the same way as Experiment 1. The evaluation results of Examples 9 to 11 are shown in Table 3.
[0126] (Examples 12 to 14)
[0127] In Examples 12 to 14, the Si content in the segregation phase 21 was changed. When preparing the powder for segregation, the Si content was controlled by adjusting the mixing ratio of the starting materials (CaCO3 powder, SrCO3 powder, MnCO3 powder and SiO2 powder). The experimental conditions other than the above were the same as those of Example 3 of Experiment 1, and capacitor samples of Examples 12 to 14 were prepared. The total Si content in each of Examples 12 to 14 was measured using STEM-EDX, and the capacitor samples of Examples 12 to 14 were evaluated in the same manner as Experiment 1. The evaluation results of Examples 12 to 14 are shown in Table 4.
[0128] Table 2
[0129]
[0130] Table 3
[0131]
[0132] Table 4
[0133]
[0134] From the evaluation results of Examples 4 to 8 shown in Table 2, it can be seen that by setting the content of Mn in the segregation phase 21 to 5 mol% or more, the impact resistance becomes particularly good, and cracks and defects can be more effectively suppressed. In addition, from the evaluation results of Examples 4 to 8, it can be seen that by setting the content of Mn in the dielectric particles 20 to 2 mol% or less, the insulation breakdown voltage is further improved.
[0135] From the evaluation results of Examples 9 to 11 shown in Table 3, it is understood that by setting the total content of Ca and Sr in the segregation phase 21 to 60 mol % or more, the impact resistance becomes particularly good, and cracks and defects can be more effectively suppressed.
[0136] From the evaluation results of Examples 12 to 14 shown in Table 4, it is understood that by setting the Si content in the segregation phase 21 to 20 mol % or more, the impact resistance becomes particularly good, and cracks and defects can be more effectively suppressed.
[0137] Experiment 3
[0138] In Experiment 3, capacitor samples of Examples 15 to 19 with different contents of the segregation phase 21 were prepared. The content of the segregation phase 21 was controlled by the mixing ratio of the segregation powder in the dielectric paste. In Experiment 3, capacitor samples of Examples 20 to 24 with different average particle sizes of the segregation phase 21 were prepared. The average particle size of the segregation phase 21 was controlled by the pulverization conditions when the segregation powder was pulverized by a ball mill after pre-sintering. In addition, the content of the segregation phase 21 was determined by using STEM-EDX to be a total of 10 μm 2 The average grain size of the segregation phase 21 is calculated by measuring the equivalent circle diameters of 20 segregation phases 21.
[0139] The experimental conditions other than those described above in Experiment 3 were the same as those in Example 3 of Experiment 1. The evaluation results of Examples 15 to 19 are shown in Table 5, and the evaluation results of Examples 20 to 24 are shown in Table 6.
[0140] Table 5
[0141]
[0142] Table 6
[0143]
[0144] From the results of Examples 15 to 19 shown in Table 5, it can be seen that by setting the content of the segregation phase 21 to 0.05 pieces / μm 2 Above and 0.50 pieces / μm 2In the following ranges, a high dielectric breakdown voltage can be maintained and cracks and defects can be suppressed more effectively.
[0145] From the results of Examples 20 to 24 shown in Table 6, it is understood that by setting the average grain size of the segregation phase 21 to within the range of 0.05 μm or more and 1.00 μm or less, it is possible to more effectively suppress cracks and defects while maintaining a high breakdown voltage.
[0146] Description of Reference Numerals
[0147] 2…Multilayer ceramic capacitors
[0148] 4…Component body
[0149] 4a…end face
[0150] 4b…side
[0151] 10…Ceramic layer
[0152] 12…Internal electrode layer
[0153] 20…Dielectric particles
[0154] 21…Segregation phase
[0155] 22…Grain Boundary
[0156] 22a…Multiple focus points on grain boundaries
[0157] 22b…Two-particle boundary
[0158] 6…External electrode.
Claims
1. A dielectric composition, wherein: have: Dielectric particles containing Ca and / or Sr; and A segregation phase containing Mn, Si, O, and at least one selected from Ca and Sr, Ca, Sr, Zr, Mn, Si, Al, Ti and Hf are set as specific elements, The total content of the specific elements in the segregated phase is 100 mol%, The Mn content in the segregated phase is 5 mol% or more.
2. The dielectric composition according to claim 1, wherein The dielectric particles contain a perovskite compound represented by ABO3, The A site of the perovskite compound contains Ca and / or Sr, and the B site contains Zr and / or Ti. The total molar ratio of Ca and Sr relative to 1 mol of A site is 0.8 or more. The molar ratio of Zr relative to 1 mol of the B site is 0.8 or more.
3. The dielectric composition according to claim 1 or 2, wherein The total content of the specific elements in the dielectric particles is 100 mol%. The Mn content in the dielectric particles is 2 mol% or less.
4. The dielectric composition according to claim 1 or 2, wherein Ca, Sr, Zr, Mn, Si, Al, Ti and Hf are set as specific elements, The total content of the specific elements in the segregated phase is 100 mol%, The total content of Ca and Sr in the segregation phase is 60 mol% or more.
5. The dielectric composition according to claim 1 or 2, wherein Ca, Sr, Zr, Mn, Si, Al, Ti and Hf are set as specific elements, The total content of the specific elements in the segregated phase is 100 mol%, The Si content in the segregated phase is 20 mol% or more.
6. The dielectric composition according to claim 1 or 2, wherein The content of the segregated phase is 0.05 per μm. 2 Above and 0.5 / μm 2 the following.
7. The dielectric composition according to claim 1 or 2, wherein The average grain size of the segregation phase is 0.05 μm or more and 1.00 μm or less.
8. A laminated ceramic electronic component, wherein: A dielectric composition comprising the dielectric composition according to any one of claims 1 to 7.
